Biospeciation of Potential Vanadium Drugs of Acetylacetonate in the Presence of Proteins - Sciortino, Giuseppe; Ugone, Valeria; Sanna, Daniele; Lubinu, Giuseppe; Ruggiu, Simone; Maréchal, Jean-Didier; Garribba, Eugenio (Frontiers in Chemistry, 2020)
Among vanadium compounds with potential medicinal applications, [VIVO(acac)2] is one of the most promising for its antidiabetic and anticancer activity. In the organism, however, interconversion of the oxidation state to +III and +V and binding to proteins are possible. In this report, the transformation of VIII(acac)3, VIVO(acac)2 and VVO2(acac)2– after the interaction with two model proteins, lysozyme (Lyz) and ubiquitin (Ub), was studied with ESI-MS (ElectroSpray Ionization-Mass Spectroscopy), EPR (Electron Paramagnetic Resonance) and computational (docking) techniques. It was shown that, in the metal concentration range close to that found in the organism (15-250 mM), VIII(acac)3 is oxidized to VIVO(acac)+ and VIVO(acac)2, which – in their turn – interact with proteins to give n[VIVO(acac)]–Protein and n[VIVO(acac)2]–Protein adducts. Similarly, the complex in the +IV oxidation state, VIVO(acac)2, dissociates to the mono-chelated species VIVO(acac)+ which interacts with Lyz and Ub. Finally, VVO2(acac)2– undergoes complete dissociation to give the 'bare' VVO2+ ion that forms adducts n[VVO2]–Protein with n = 1-3. Docking calculations allowed the prediction of the residues involved in the metal binding. The results suggest that only the VIVO complex of acetylacetonate survives in the presence of proteins and that its adducts could be the species responsible of the observed pharmacological activity, suggesting that in these systems VIVO2+ ion should be used in the design of potential vanadium drugs. If VIII or VVO2 potential active complexes are designed, species with high redox and thermodynamic stability must be synthesized to prevent oxidation and dissociation, modulating adequately the features of the organic ligand.